Challenges Faced by B.P.L. Population in Availing Public Healthcare – Analysing Government Initiatives, Technology and Cultural Barriers in Aligarh District, U.P - Afzal, Fahad; Raychaudhuri, P.S.; Afzal, Mohd Atif; Ahmad, Afaq Amir (South Asian Journal of Social Sciences and Humanities, 2021)
Public healthcare and government health initiative have always been in question regarding their availability, efficiency, and quality. This matter most for the poor section of society who have to go through various hurdles to avail the basic treatment, besides financial problems. The aim of this survey study was to analyze the present scenario of public healthcare system and the challenges in availing public healthcare faced by BPL (Below Poverty Line) and low-income population of Uttar Pradesh. A cross-sectional survey (direct interview) of 104 respondents was conducted in March 2021. Thematic analysis of generated qualitative data was done using ATLAS.ti (version 9.0.15). The quantitative data was analyzed by using SPSS (version 22.0.0.0). The respondents were from 2 rural areas near the Aligarh district in UP. The secondary data from published research articles and government sources were also analyzed. Analysis of data revealed there are various challenges faced by low-income population while availing public healthcare services. The nature of challenges has a considerable variation, from lack of information to documents’ unavailability, from technical issues in government schemes to cultural pressure. Data analysis revealed, the majority of respondents (59%) faced one or more types of challenges during treatment from public health facilities. Awareness level is identified as a significant problem among respondents. Analysis of secondary data and literature review revealed uneven resource allocation and discrepancies in government initiatives toward UHC (Universal Health Coverage). Results indicated the contrasting nature of healthcare in Uttar Pradesh. Data analysis revealed the disparity of ‘average OOP travelling expenditure’ for male and female. The correlation analysis revealed that there is negative correlation (y = -0.1377x + 11.119) of ‘age of respondent’ and ‘average satisfaction from public health service’ (r = -0.911; R² = 0.8301). This research article provides the evidence that there exists a communication gap between policymakers and end-users (BPL & low-income section). This article underscored some technical flaw in the UHC policies that act as a barrier for low
Keywords: Public Health; Challenges; BPL; Poverty; Universal Health Coverage; Uttar Pradesh; Low Income